2018
DOI: 10.1155/2018/9412676
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram Syndrome: A Case Report and Review of Clinical Manifestations, Genetics Pathophysiology, and Potential Therapies

Abstract: Background Classical Wolfram syndrome (WS) is a rare autosomal recessive disorder caused by mutations in WFS1, a gene implicated in endoplasmic reticulum (ER) and mitochondrial function. WS is characterized by insulin-requiring diabetes mellitus and optic atrophy. A constellation of other features contributes to the acronym DIDMOAD (Diabetes Insipidus, Diabetes Mellitus, Optic Atrophy, and Deafness). This review seeks to raise awareness of this rare form of diabetes so that individuals with WS are identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Nonsyndromic diabetes has also been reported with homozygosity for a nonsynonymous variant frequently found in Ashkenazi Jewish individuals (20), but it is clearly not confined to that variant. The therapeutic implications of this diagnostic reassignment remain to be seen, but successful use of incretin interventions has been reported (21,22). It should definitely be included in all monogenic diabetes panels.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsyndromic diabetes has also been reported with homozygosity for a nonsynonymous variant frequently found in Ashkenazi Jewish individuals (20), but it is clearly not confined to that variant. The therapeutic implications of this diagnostic reassignment remain to be seen, but successful use of incretin interventions has been reported (21,22). It should definitely be included in all monogenic diabetes panels.…”
Section: Discussionmentioning
confidence: 99%
“…However, atypical cases have been reported. Perhaps most notably, a woman with a history of optic atrophy at 10 years, SNHL, dizziness, and unsteady gait at 25 years, and gestational diabetes mellitus at 39 years was found to carry biallelic WFS1 mutations 4. While most reported cases of Wolfram syndrome follow the more typical pattern described above, only 28% of cases demonstrate the full DIDMOAD phenotype 2.…”
Section: Introductionmentioning
confidence: 94%
“…WFS1 expression has been shown to be induced during insulin secretion, suggesting that WFS1 is an important component of proinsulin folding and processing in the ER of the β-cell [3840]. Other studies suggested that WFS1 can also regulate Ca 2+ signal transduction processes, thus influencing the storage of cellular ER calcium levels and, consequently, cells apoptosis [28, 41]. WFS1-deficient β-cells and neurons have reduced Ca 2+ in ER and increased cytosolic Ca 2+ levels, a condition that leads to activation of the Ca 2+ -dependent cysteine protease calpain and cell death [42, 43].…”
Section: Etiology: Genetic Background Molecular Biology and Pathophymentioning
confidence: 99%
“…Recently, it has been suggested that doses < 200 mg/day may be safely used in patients without co-existing liver dysfunction or co-ingestion of hepatotoxic medications. There is also a phase 1 clinical trial currently investigating the safety of dantrolene long-term use in WS patients (A Clinical Trial of Dantrolene Sodium in Pediatric and Adult Patients with Wolfram Syndrome, ClinicalTrials.gov, NCT02829268) [28, 74]. Given that WFS1 can bind SERCA, a protein that regulates calcium homeostasis, a therapeutic strategy could be the development of molecules targeting SERCA in order to increase and maintain high calcium levels in ER.…”
Section: Treatment and New Perspectivesmentioning
confidence: 99%